Organizational Citizenship Behavior and Role Breadth: A Meta‐Analytic and Cross‐Cultural Analysis. Issue 5 (18th September 2013) - Jiao, Changquan; Richards, David A.; Hackett, Rick D.
Abstract We provide a meta‐analysis of the empirical literature concerning role breadth, defined as the degree to which employees consider organizational citizenship behavior (OCB) to be an inherent part of their job. Results based on a combined sample size of 9, 222 showed: (a) Confucian Asians consider OCB as part of their job to a greater extent than do their Anglo counterparts; (b) affiliative kinds of OCB (e.g., helping, conscientiousness, and courtesy) are more likely to be considered part of one's job than are change‐oriented OCB (e.g., voice, taking charge, and initiative); and (c) OCB‐inclusive role breadth correlates strongly with OCB (rc = .43). The implications of these findings for human resources practice, such as competency modeling, employee selection and training, organizational rewards, and employee‐employer/supervisor relations, are discussed. © 2013 Wiley Periodicals, Inc.